2016
DOI: 10.1108/ir-10-2015-0190
|View full text |Cite
|
Sign up to set email alerts
|

On designing an active tail for legged robots: simplifying control via decoupling of control objectives

Abstract: Abstract-This work explores the possible roles of active tails for steady-state legged-locomotion. A series of simple models are proposed which capture the dynamics of an idealized running system with an active tail. The models suggest that the control objectives of injecting energy into the system and stabilizing body-pitch can be effectively decoupled via proper tail design: a long, light tail. Thus the overall control problem can be simplified, using the tail exclusively to stabilize body-pitch: this effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…While reproducing weightlessness conditions in 3D space on Earth remains a challenge, several research initiatives have resulted in interesting experimental work. For instance, the results in [24], [25], [26] show that a tailed robot can effectively accomplish inertial reorientation in at least one plane. The in-depth analysis of [27] and the simulations in [28] concluded that the use of a tail or appendages is particularly interesting for terrestrial robots and also explored the use of flailing limbs.…”
Section: Global Rotationmentioning
confidence: 99%
“…While reproducing weightlessness conditions in 3D space on Earth remains a challenge, several research initiatives have resulted in interesting experimental work. For instance, the results in [24], [25], [26] show that a tailed robot can effectively accomplish inertial reorientation in at least one plane. The in-depth analysis of [27] and the simulations in [28] concluded that the use of a tail or appendages is particularly interesting for terrestrial robots and also explored the use of flailing limbs.…”
Section: Global Rotationmentioning
confidence: 99%
“…The updated version of Salto, Salto-1p makes use of a reaction wheel and fans to stabilize and steer the robot [13]. The use of a tail was explored with the 2.5 kg Jeorba hopper [14] and the 1.25 kg Cheetah-Cub [15]. A reaction wheel was proposed during a simulation study to stabilize the pronking motion of a 10 kg quadruped on compliant terrain [16].…”
Section: Introductionmentioning
confidence: 99%
“…They proved that an active tail can both greatly improve forward velocity and reduce body pitch per stride. 8 In addition, the tail plays an important role in free-falling robots 9 and bionic lizards running on the water. 10 In most studies, the tail is made of a rigid rod, but there are exceptions.…”
Section: Introductionmentioning
confidence: 99%